THE EFFECTIVENESS OF ONLINE LEARNING PROCESS IN THE COVID-19 PANDEMIC ON ELASTICITY TOPIC - Ramadhani, Aulia; Siregar, Alkhafi Maas (UNIVERSITAS NEGERI MEDAN, 2022)
This research aims to: 1) knowing the student's response to online learning process on elasticity topic during pandemic COVID-19, 2) knowing the teachers response to online learning process on elasticity topic during pandemic COVID-19, and 3) knowing the effectiveness of online learning process on elasticity topic carried out during the COVID-19 pandemic. This type of research is quantitative using a survey method. The instrument used was a student questionnaire and a teacher questionnaire in the form of a Likert scale. The results showed that the responses of both students and teachers to online learning on elasticity topic based on the criteria, i.e., online learning planning, processes, and evaluations, on average could be categorized as good, the effectiveness of online learning on elasticity topic can be categorized as effective, level of student mastery and the level of learning completeness can be categorized as good and complete, but there are still many difficulties during the implementation process.